高效液相色谱法测定玉米植物甾醇中 豆甾醇、菜油甾醇和β-谷甾醇 Determination of stigmasterol, campesterol and β-sitosterol in corn sterols by high performance liquid chromatography - 刘景凡,孙聪,梁少华 LIU Jingfan, SUN Cong, LIANG Shaohua (Zhongguo youzhi)
旨在为玉米植物甾醇的实际生产或深度开发利用奠定基础，建立了一种同时测定玉米植物甾醇中豆甾醇、菜油甾醇和β-谷甾醇的高效液相色谱检测方法。采用Waters Symmetry C18色谱柱(4.6 mm×250 mm，5 μm)，二极管阵列检测器，检测波长205 nm，甲醇-水(体积比92∶ 8)为流动相进行检测，外标法进行定量。结果表明：3种甾醇单体在125~2 000 μg/mL质量浓度范围内线性关系良好，检出限均不大于0.07 μg/mL；3种甾醇单体的峰面积和保留时间的相对标准偏差（RSD）在仪器精密度实验中介于0.24%~1.23%，在样品重复性实验中介于0.61%~2.38%，在日内稳定性实验中介于0.13%~2.92%，在日间稳定性实验中介于0.67%~3.43%；3种甾醇单体的加标回收率在76.86%~105.74%之间，RSD均小于5%。综上，该方法具有灵敏度高、准确性好、操作简便、稳定性好的特点，可实现玉米植物甾醇中豆甾醇、菜油甾醇和β-谷甾醇的定量分析。 Aiming to lay the foundation for the actual production or deep exploitation and utilization of corn sterols, a high performance liquid chromatography (HPLC) method was established for the simultaneous determination of stigmasterol, campesterol and β-sitosterol in corn sterols. The separation was performed on a Waters Symmetry C18 column (4.6 mm×250 mm, 5 μm) with a diode array detector at a detection wavelength of 205 nm, and methanol-water (volume ratio 92∶ 8) as the mobile phase, and the analytes was quantified by external standard method. The results showed that the linearity of the three sterol monomers was good in the range of 125-2 000 μg/mL, and the detection limits were not more than 0.07 μg/mL for all of them. The relative standard deviations (RSD) of the peak area and retention time of the three sterol monomers ranged from 0.24% to 1.23% in the instrumental precision experiments, from 0.61% to 2.38% in the sample reproducibility experiments, from 0.13% to 2.92% in the intra-day stability experiments, and from 0.67% to 3.43% in the inter-day stability experiments. The recoveries of the three sterol monomers ranged from 76.86% to 105.74%, and the RSD were less than 5%. In conclusion, the method is characterized by high sensitivity, good accuracy, easy operation and good stability, and can realize the quantitative analysis of stigmasterol, campesterol and β-sitosterol in corn sterols.